Data de plantio de gladíolo para comercialização em dois picos de consumo no clima atual e em climas futuros no Rio Grande do Sul utilizando o modelo - Becker, Camila Coelho (2017)
Gladiola (Gladiolus x grandiflorus Hort.) is an important cut flower cultivated under field conditions. The air temperature is the main abiotic factor that drives their phenology, therefore the scheduling flowering of gladiola for target markets by defining the optimum planting date. The objective this study was determine the optimum planting date of gladiola aiming harvest spikes for selling on All Souls’ Day and Mother’s Day under current climate and in CMIP5 scenarios in the Rio Grande do Sul State. The PhenoGlad model was used for simulates the developmental stages of gladiola and plant injuries by heat and frost. For simulates the optimum planting date under current climate, input data in the model was minimum and maximum daily temperature of 55 years (1961-2015) from eighteen weather stations across the State. Once optimum planting date was simulated for each maturation group and weather station, with all years, the planting date was averaged for each El Niño Southern Oscillation (ENSO) phases to access the ENSO effect on the optimum planting date of gladiola. For simulates the optimum planting date under climate scenarios, input data in the model was minimum and maximum daily temperature of the 32 grid points in the State, for RCP2.6, RCP4.5 and RCP8.5 scenarios. The optimum planting date in the future period (2070-2098) was presented as anomalies (difference between the optimum planting date and average optimum planting date in the baseline period (1976-2005) for each grid point and maturation group. The percentage of years with damage was also presented as anomalies. The phenomenon ENSO affects the optimum planting date of gladiola for harvesting on All Souls’ Day. For this growing season, planting date was anticipated for La Niña years (low temperatures) and delayed for Very Strong El Niño (high temperatures). For Mother’s Day, only Very Strong El Niño events affect the development of the gladiola, but different of the growing season for All Souls’ Day, planting date was anticipated for Very Strong El Niño years, and delayed for others ENSO phases. As well as for Very Strong El Niño years, for harvesting on All Souls’ Day, the optimum planting date was delayed in the climate scenarios, due to shortening of the cycle on rising temperatures conditions. For Mother’s Day, the average air temperature exceeded the optimum temperature of the crop in the warmest regions of the State. In these regions, the anomalies of the optimum planting date were negatives because the development rate decreased, delaying flowering. The risk of injuries by heat is more severe in the growing season for harvesting on All Souls’ Day, mainly in the scenario RCP8.5 and warmest regions, where the anomalies reached +70% of years. This results will provide subsidies for the production expansion for others regions of the State in order to harvesting spikes for selling on All Souls’ Day and Mother’s Day.